Neurorestoration Approach by Biomaterials in Ischemic Stroke - Esteban-Garcia, Noelia; Nombela, Cristina; Garrosa, Javier; Rascón-Ramirez, Fernando J.; Barcia, Juan Antonio; Sánchez-Sánchez-Rojas, Leyre (Frontiers in Neuroscience, 2020)
Ischemic stroke is the leading cause of disability in the western world, assuming a high socio-economic cost. One of the most used strategies in the last decade has been biomaterials, which have been initially used with a structural support function. They have been perfected, different compounds have been combined and they have been used together with cell therapy or controlled release chemical compounds. This double function has driven them as potential candidates for the chronic treatment of ischemic stroke. In fact, the most developed are in different phases of clinical trial. In this review we will show the ischemic scenario and address the most important criteria to achieve a successful neuroreparacion from the point of view of biomaterials. The spontaneous processes that are activated and how to enhance them is one of the keys that contributes to the success of the therapeutic approach. In addition, the different routes of administration and how they affect the design of biomaterials are analyzed. Future perspectives show where this broad scientific field is heading, which advances every day with the help of technology and advanced therapies.